Tumors of the Gnathic System with Multiple Histogenetic Characteristics - Kurt, Friedman; Tamara, Luis; Velez, Ines (Journal of Diseases, 2016)
Background: There is a great confusion in the scientific literature regarding tumors composed of tissues with different histogenetic and molecular characteristics. Diagnosis of a neoplasm composed of more than one tumoral tissue can be extremely challenging, so is the treatment. Methods: This is an attempt, illustrated with several examples of these types of tumors from the gnathic system, to gain a better understanding of this issue. Conclusions: As the best of our knowledge, this is the first report of a collision tumor between a sarcomatoid carcinoma and so called keratocystic odontogenic tumor. It is critical to understand these types of tumors, for correct diagnosis, staging and treatment.